2015
DOI: 10.1007/s11427-015-4877-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing-based genome-wide identification of microRNAs expressed in developing cotton seeds

Abstract: MicroRNAs (miRNAs) have been shown to play critical regulatory roles in gene expression in cotton. Although a large number of miRNAs have been identified in cotton fibers, the functions of miRNAs in seed development remain unexplored. In this study, a small RNA library was constructed from cotton seeds sampled at 15 days post-anthesis (DPA) and was subjected to high-throughput sequencing. A total of 95 known miRNAs were detected to be expressed in cotton seeds. The expression pattern of these identified miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
6
0
1
Order By: Relevance
“…It has been reported that most sRNAs functioning as small interfering RNAs (siRNAs) are 24 nt long (Rajagopalan et al, 2006); the appearance of such large numbers of 24 nt sRNAs in the four small RNA libraries indicated that siRNAs accounted for a large proportion in the sRNA datasets. These results are in agreement with previous reports on cotton (Wang et al, 2015) and other plants such as rice (Li et al, 2011), maize (Kang et al, 2012), and Medicago truncatula (Szittya et al, 2008). …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…It has been reported that most sRNAs functioning as small interfering RNAs (siRNAs) are 24 nt long (Rajagopalan et al, 2006); the appearance of such large numbers of 24 nt sRNAs in the four small RNA libraries indicated that siRNAs accounted for a large proportion in the sRNA datasets. These results are in agreement with previous reports on cotton (Wang et al, 2015) and other plants such as rice (Li et al, 2011), maize (Kang et al, 2012), and Medicago truncatula (Szittya et al, 2008). …”
Section: Resultssupporting
confidence: 94%
“…Advances in the understanding of miRNA-mediated gene regulation revealed that miRNAs play important roles in plant developmental switching and plant responses to environmental abiotic and biotic stresses as well as signal transduction (Jones-Rhoades et al, 2006; Li and Zhang, 2016). To date, several studies have investigated many miRNAs and their regulatory functions in the developmental processes of cotton fibers (Wang et al, 2012, 2015; Xue et al, 2013; Liu et al, 2014; Yu et al, 2014; Xie et al, 2015). Both computational prediction and experimental examinations have been widely employed to identify miRNAs in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012) detected 125 and 127 known miRNAs in maize seeds and leaves, respectively20; and Wang et al . (2015) discovered 95 known miRNAs and 23 novel miRNA candidates in cotton seeds30. Here, in our study, 94 known and 3 novel miRNAs were identified in C. gynandra , and 102 known and 3 novel miRNAs were identified in C. hassleriana .…”
Section: Discussionsupporting
confidence: 56%
“…Sequencing was done on the Illumina platform generating paired end reads of 100 bp each. Raw reads were filtered and trimmed based on quality and adapter inclusion using the SOAPnuke 1.5.0 software (http://soap.genomics.org.cn/) [62]. After filtering, the remaining reads are called ‘clean reads’ and stored in FASTQ.…”
Section: Methodsmentioning
confidence: 99%